The theory of economic development: an inquiry into profits, capital, credit, interest, and the business cycle - Schumpeter, Joseph A.; Opie, Redvers (New York: Cambridge University Press, 1961)
The book covers the following topics: The Circular Flow of Economic Life as Conditioned by Given Circumstances; The Fundamental Phenomenon of Economic Development; Credit and Capital; Entrepreneurial Profit; Interest on Capital; and The Business Cycle.
rpm 03/11/2017
Loans
Keywords: Economics; Economic history